A Decade in View : A Cross-Country Panel Analysis of the Institutional Impact on Real Per Capita GDP Growth From 2010-2022 - Bdour, Yousef; Chytilová, Helena; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
The thesis at hand investigates the impact of institutional quality on real per capita GDP growth across a random sample of 32 countries from 2010 to 2022. Using the World Governance Indicators, six dimensions of institutional quality, political stability, government effectiveness, rule of law, regulatory quality, voice and accountability, and control of corruption, are all integrated into a composite institutional quality indicator using Principal Component Analysis, to provide a comprehensive assessment. The empirical analysis utilises a cross-country panel regression using various econometric models, including Pooled OLS, Fixed Effect, Random Effects, and ultimately Generalised Least Squares, ensuring a high degree of robustness by addressing data-specific challenges. The results of the analysis highlight the importance of institutions as drivers of economic growth, finding a positive and significant role on real GDP per capita, along with human capital. Contrarily, geography and trade openness where both demonstrated to be insignificant when other variables are considered.
Vedoucí práce: Helena Chytilová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses